﻿A new species of frog (Terrarana, Strabomantidae, Phrynopus) from the Peruvian Andean Grasslands - Germán Chávez; Luis A. García-Ayachi; Alessandro Catenazzi (Evolutionary Systematics, 2023)
We describe a new terrestrial frog from the puna grasslands adjacent to the Mantaro dry valley in southern Peru. Phrynopus apumantarum sp. nov. is similar in appearence to P. bufoides but is differentiable by lacking discoidal fold and enlarged warts on dorsum, lacking a prominent post ocular fold and having canthal and post ocular stripe. Lastly, we propose to place the new species under the Vulnerable (VU) category of the IUCN Red List, due its small distribution and habitat loss recorded at the type locality.